Seismic response of monopile foundation of offshore wind turbines under near-field and far-field ground motions - Sahraeian, S. Mohammad Sadegh; Masoumi, Mohammad Ali; Najafgholipour, Mohammad Amir; Shafiee, Ali; Pandey, Bishnu (Soil dynamics and earthquake engineering (1984), 2023)
The tendency to use renewable energy sources has been increased due to the problems associated with utilization of the fossil fuels such as their instability in the future and environmental issues. Offshore wind turbines (OWTs) have become a major renewable energy source due to their merits. However, many of the offshore wind farms planned recently are located in the seismic prone areas, which introduces some challenges regarding their foundation design while, the most common OWTs’ foundation by far, is monopile. OWTs are tall infrastructures with a longer natural period than the predominant period of most earthquakes. While far-field earthquakes have a large predominant period which might amplify the structure response and cause significant damage to OWTs, near-field earthquakes with large pulse period might lead to large residual displacements, especially in OWTs that wind could exert an eccentric load. In this study, seismic behavior of the National Renewable Energy Laboratory (NREL) 5 MW offshore wind turbine on monopile foundation embedded in liquefiable soil is investigated under near-field and far-field earthquakes using finite element computer program OpenSees. The seismic response of the structure was also evaluated under bidirectional excitation corresponding to the Kobe earthquake, Japan. Considering the lateral displacement of the superstructure, rotation, settlement, and bending moment of the monopile and shear stress/strain, and excess pore water pressure in the ground, a comparison between the seismic behavior of the monopile foundation of the offshore wind turbine under near-field and far-field earthquakes was performed. The results of this study showed that the seismic response of the monopile-superstructure system under near-field earthquakes was more critical despite the shorter duration and the smaller arias intensity of those earthquakes. It highlighted the remarkable effect of the other parameters such as near-field pulse which contained a lot of energy. Furthermore, the seismic response of the monopile was enhanced under the bidirectional earthquake loading. •The seismic response of monopile foundation of an offshore wind turbine embedded in a liquefiable soil was investigated under near-field and far-field earthquakes through a finite element modeling conducted in OpenSees platform.•The seismic behavior of the monopile-superstructure under near-field earthquakes was more critical despite the short duration and the small arias intensity of the near-field earthquakes.•The superstructure maximum drift, monopile rotation, and bending moment were larger in the near-field earthquakes with respect to far-field earthquakes. Meanwhile the foundation settlement was higher during the far-field earthquakes.•The effect of the near-field pulse was observed with a spike at the beginning of the time history of some response parameters including the superstructure drift, monopile rotation and bending moment. This phenomenon could lead to a sudden failure in the structure or its foundation.•Although the arias intensity of the near-field earthquakes is smaller, the variation in the shear stress-strain response of the foundation soil around the monopile is larger during these earthquakes. It could be the main reason for the larger lateral response of the monopile during the near-field earthquakes.